Decolonizing citizenship learning with international students: Exploring the possibilities through photovoice - Perry, J. Adam; Bethune, L. Rachael (Journal of International Students, 2023)
This article explores the possibilities for decolonizing approaches to inter-cultural learning for international students in Canada. In this article the authors present the findings from a series of photovoice workshops conducted as a part of a larger mixed-methods project that explores how informal and everyday pedagogies shape international students’ mobility decisions in the Atlantic Canadian province of Nova Scotia. Participants’ collaborative analysis of their own photographs reveal how everyday citizenship learning emerges from international students’ affective relationships to place in such a way that obscures how international education is implicated in processes of settler colonialism. However, evidence suggests that participants’ sense of belonging is deeply implicated in their connections to place, highlighting potential opportunities for integrating international students in current initiatives to “decolonize” higher education in the Canadian context.